Students’ Well-Being Assessment at School - Nurul Hidayah Hidayah; Marthen Pali; Muhammad Ramli,; Fattah Hanurawan (Journal of Educational, Health and Community Psychology, 2016)
Abstract This research aims at describing students’ well-being assessment at two private secondary schools in Sleman regency, Yogyakarta Special Province, Indonesia. The subjects of the research were 42 secondary school students in the area. This is an evaluative research by means of quantitative approach. The data collecting technique employed a focus group discussion (FGD) while the instrument used an FGD guide book based on a School Well-being Model (Konu and Rimpela, 2002). The data were analyzed quantitatively by means of thematic analysis. The research finding showed that the students’ school well-being was psychologically high at dimension of health status, but low at dimension of having, loving, and being. Another important finding is that there was a tendency of verbal, physical, as well as sexual bullying done by their classmates and teachers personally. Key words: well-being, psychological well being, school, and student